DIGITAL LITERACY STUDY: KNOWLEDGE AND COMMUNICATION SKILLS AMONG TEENAGERS - Syarifuddin Syarifuddin; Mohammad Ahmad Bani Amer; Indah Sulistiani (INJOSEDU: International Journal of Social and Education, 2025)
Digital literacy encompasses the ability to access, understand and use digital information effectively, which is becoming increasingly important in an era of rapidly evolving technology. This study uses the literature method. The results showed that most teenagers have good access to digital devices such as smartphones and computers. However, there are variations in their level of digital knowledge and skills, especially when it comes to using technology for productive purposes. Formal education that supports digital literacy proved to be important, along with the significant role of support from family and peers in directing the wise use of technology. Thus, improving digital literacy and communication skills among adolescents requires synergy between adequate technological infrastructure, relevant education, and support from the social environment. Thus, adolescents can be better prepared to face challenges in the digital era and utilise technology optimally and responsibly.